Elevated hemoglobin A1c is associated with readmission but not complications. (September 2014) - Engoren, Milo; Schwann, Thomas A; Habib, Robert H
Background: studies have shown that elevated hemoglobin A1c levels are associated with worse short-term outcomes after cardiac surgery. However, the effect on readmission has not been studied. The primary purpose of this study was to determine the independent effect of hemoglobin A1c level on the readmission rate after cardiac surgery. The secondary purpose was assess its effect on complications and mortality. Methods: consecutive patients undergoing coronary artery bypass surgery between April 2007 and August 2010 were divided into 3 groups based on preoperative hemoglobin A1c levels. Outcomes were controlled for demographics, comorbidities, and surgery. Results: 300 (34%) patients had normal hemoglobin A1c levels (<6.0%), 305 (35%) had mildly elevated levels (6.0%–6.9%), and 275 (31%) had markedly elevated levels (≥7.0%). Postoperative glucose levels were similar among all 3 hemoglobin A1c groups. Compared to patients with normal hemoglobin A1c levels, those with higher levels were more likely to be readmitted: adjusted odds ratio 2.091 (95% confidence interval: 1.074–4.069, p  = 0.036) for hemoglobin A1c 6.1%–6.9%; and adjusted odds ratio 2.089 (95% confidence interval: 1.050–4.155, p  = 0.036) for hemoglobin A1c ≥ 7.0. Overall, 381 (43%) patients suffered complications, and hemoglobin A1c levels were similar in those with and without complications (6.8% ± 1.6% vs. 6.9% ± 1.7%, p  = 0.837). Mortality was equivalent in all 3 hemoglobin A1c groups. Conclusions: elevated preoperative hemoglobin A1c levels are associated with an increased risk of readmission but not complications.